Ex-situ modification of bacterial cellulose for immediate and sustained drug release with insights into release mechanism. (1st December 2020) - Adepu, Shivakalyani; Khandelwal, Mudrika
Graphical abstract: Highlights: Two drying methods are used to tune drug release kinetics from bacterial cellulose. Swellability (rate, extent), and porosity directly affected the diffusion of drug. Oven-dried BC shows sustained release, while freeze-dried BC showed a burst release. Abstract: The release of drug from bacterial cellulose (BC) is tuned to achieve immediate and controlled delivery by using two drying strategies: freeze-drying and oven-drying. Diclofenac sodium (DCF), a hydrophilic drug, was used as the model drug and was loaded in oven-dried BC (BC-OD-DCF) and freeze-dried BC (BC-FD-DCF) to obtain sustained release and burst release, respectively. BC dried by the two methods were characterized and found to possess different structures and morphologies. The crystallinity was found to be higher for BC-OD (86 % for BC-OD and 79 % for BC-FD) while BC-FD offered higher porosity (92 % for BC-FD and 75 % for BC-OD), higher specific surface area (85 m 2 /g for BC-FD and 35 m 2 /g for BC-OD) and pore size, which altogether affects the matrix swellability, drug loading and release behaviour. The mathematical modelling of drug release kinetics supports diffusion-driven first-order release from BC-FD-DCF whereas release from BC-OD-DCF shows a super case II transport, where the buffer front travels slowly into the denser oven-dried matrix leading to a controlled release of the drug. The correlation between swelling and cumulative drug release is also discussed.